Controle Biológico de Sclerotinia sclerotiorum (Lib.) de Bary e Promoção de Crescimento de Plantas de Feijão por cepas de Trichoderma spp. isoladas em Mato Grosso do Sul - Clarice Rossato Marchetti (2021)
The present work comprised the investigation of 57 isolates of Trichoderma spp., isolated from the soil of Mato Grosso do Sul, or endophytic from the plant species Bauhinia ungulata, Aspilia grazielae and Vockysia divergens, native to the Pantanal and Cerrado of MS, regarding their capacity to inhibit the growth and spread of the phytopathogen Sclerotinia sclerotiorum. Confrontation tests, culture in paired plates and cell wall degrading enzymes (CWDEs) activity assays were performed. All showed significant results in growth inhibition against S. sclerotiourm. Eight strains were tested on the phytopathogens Fusarium sp, Macrophomina phaseolina, and Rhizoctonia solani, showing a high growth inhibition rate. As for the production of CWDEs, the 57 strains tested in this work showed a high specific activity of β-1,3-glucanases and proteases enzymes. In the protection test for disease severity (white mold), after spraying the phytopathogen (S. sclerotiorum) on the leaves of bean plants, the treatments with strains T25 and T55 stand out, which provided 90 to 100% protection against the disease. Tests with the addition of the phytopathogen in the substrate, the plants treated with strains T25 and T55 were also asymptomatic. The ability of 8 strains of Trichoderma sp to hyperparasitism of S. sclerotiorum sclerotia and their viability in carrot discs was tested. The tested strains prevented between 93 and 100% of sclerotia germination. In order to detect the presence of Trichoderma sp as an endophytic in common bean plants, the eight strains of the experiment with S. sclerotiorum in the substrate were tested, and the reisolates of T25 and T57 were characterized as similar, comparing with the inoculated strain. The ability of Trichoderma spp. to promote the growth of common bean plants was determined by comparing the total fresh and dry mass, length of roots, stem and leaf area with the control, without fungi. All treatments with the tested Trichoderma strains showed potential growth promoters, with a statistical difference between the control and the T55 and T57 strains showing the highest percentage of dry mass gain. On the other hand, the treatment with strain T46 showed plant growth inhibition. Eight isolates were selected for analysis of volatile compounds by gas chromatography (GC/MS), and some compounds were identified, such as acorenol (alkaloid), 6-pentyl-α-pyrone (lactone), β-cedrene, sesquiphelandrene, cembrene, sesquisabinene, 7-methanoazulene, a-cedrol, acorenone, epicubenol, verticellol, cadina-1,4-diene and naphthalene (terpenoids). The results obtained show that the Trichoderma strains tested have potential as biocontrol agents against S. sclerotiorum and as biostimulants, increasing plant growth and development.